Wheat cultivars response to Rhopalosiphum padi infestation - Peruzzo, Rafael; Salvadori, José Roberto; Pereira, Paulo Roberto Valle da Silva; Tonello, Étel Carmen Bertollo Lucas Simionatto (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the response of eight commercial wheat cultivars (BRS 194, BRS 208, BRS Camboatá, BRS Guabiju, BRS Guamirim, BRS Louro, BRS Timbaúva e BRS Umbu) to the infestation of Rhopalosiphum padi (Hemiptera: Aphididae). The experiment was carried out at Embrapa Trigo, in greenhouse conditions. It was used the randomized block design, in a split-plot array, with eight treatments and six replicates. The plots received treatments with or without infestation with aphids, and the split-plots were composed by the cultivars. The infestation with aphids (20 wingless adults per plant) was done 12 days after plant emergency, in the beginning of tillering, and was kept for 15 days. The cultivars responded differently to the infestation with aphids. BRS Timbaúva cultivar is more resistant, and BRS Umbu and BRS Guabiju cultivars are more susceptible to R. padi, concerning plant growth and plant yield.